(untitled) (Journal of Organizational Psychology, 2020)
This study reports a 20-year follow-up on 90 of 386 dental graduates who completed a well-validated measure of professional identity formation as entering dental students, at graduation, and as a follow-up survey 18-22 years following graduation from a large Midwest Dental School. Respondents also completed a career satisfaction questionnaire. Archival pre and posttest data were available on measures of Rest’s Four Component Model of Morality: ethical sensitivity, moral judgment, and moral implementation. Based on the results, professional identity formation was enhanced by an educational intervention, but only the authority dimension was sustained. Professional identity formation correlated positively with participants’ current career satisfaction, and with moral judgment summary scores.